2018
DOI: 10.1136/bmjopen-2017-019129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reproductive period duration and number of pregnancies on midlife ECG indices: a secondary analysis from the Women’s Health Initiative Clinical Trial

Abstract: ObjectivesPregnancy, menses and menopause are related to fluctuations in endogenous sex hormones in women, which cumulatively may alter cardiac electrical conduction. Therefore, we sought to study the association between number of pregnancies and reproductive period duration (RD, time from menarche to menopause) with ECG intervals in the Women’s Health Initiative Clinical Trials.DesignSecondary analysis of multicentre clinical trial.SettingUSA.Primary outcome measuresECGintervals: PR interval, P-wave duration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…There has only been 1 other study to show an association between parity and electrocardiographic parameters. 27 The authors reported that grand multiparity (≥5 live births) was associated with a 1.32‐ms increase in PR interval, supporting the plausibility of our findings. Pregnancy has been associated with increase in P‐wave parameters (P‐wave duration and P‐wave dispersion) when compared with controls , 28 with exaggerated changes in pathologic states, such as preeclampsia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There has only been 1 other study to show an association between parity and electrocardiographic parameters. 27 The authors reported that grand multiparity (≥5 live births) was associated with a 1.32‐ms increase in PR interval, supporting the plausibility of our findings. Pregnancy has been associated with increase in P‐wave parameters (P‐wave duration and P‐wave dispersion) when compared with controls , 28 with exaggerated changes in pathologic states, such as preeclampsia.…”
Section: Discussionsupporting
confidence: 84%
“…A large‐scale study reported that prolonged reproductive duration (age from menarche to menopause) is associated with a prolonged PR interval, suggesting a hormonal effect on cardiac conduction. 27 …”
Section: Discussionmentioning
confidence: 99%
“…For ASCVD risk score analyses, we performed multiple imputation to impute missing total cholesterol and high-density lipoprotein values because of significant missingness. 18 Total cholesterol and high-density lipoprotein along with all CHD risk factors were used in an fully conditional specification regression model, and the final results were summarized from 20 iterations of the imputation process using PROC MIANALYZE. All crosssectional models were also adjusted for cohort to reduce selection bias from the HF subcohort.…”
Section: Studymentioning
confidence: 99%
“…Parikh et al studied the effects of reproductive period duration and number of pregnancies on midlife ECG indices, reporting small but significant changes in Pwave characteristics. However, they also stated that many factors could contribute to this behavior, thus the role of sex hormones is not clear [17].…”
Section: Ecg Sexual Differences In Patients With Afmentioning
confidence: 99%